STRUCTURAL AND KINEMATICAL ANALYSIS OF MODEL OF SERIAL ROBOT - Ovidiu ANTONESCU; Mariana TROFIMESCU; Paun ANTONESCU (Fiabilitate şi Durabilitate)
The paper presents a serial robot, whose main spatial kinematic chain consists of four revolute joints. Four continuous current electric motors are used for driving the serial robot. We carried out a structural analysis of the robot, which has four mobilities, while the fourth one is redundant. We have used matrix calculus for the kinematic analysis of the serial robot arm so that we obtained the three Cartesian coordinates of the characteristic points according to the four independent angular parameters. Regarding the prehension mechanism, the kinematic schema with two symmetrical parallelograms has been presented, which ensures the circular translational motion of the two fingers.